Long-term outcomes of transvaginal mesh surgery for pelvic organ prolapse: a retrospective cohort study - Xiaojuan Wang; Yisong Chen; Changdong Hu; Keqin Hua (BMC, 2021)
Abstract Background The objective of this study was to evaluate the overall outcomes and complications of transvaginal mesh (TVM) placement for the management of pelvic organ prolapse (POP) with different meshes with a greater than 10-years of follow-up. Methods We performed a retrospective review of patients with POP who underwent prolapse repair surgery with placement of transvaginal mesh (Prolift kit or self-cut Gynemesh) between January 2005 and December 2010. Baseline of patient characteristics were collected from the patients' medical records. During follow-up, the anatomical outcomes were evaluated using the POP Quantification system, and the Patient Global Impression of Improvement (PGI-I) was used to assess the response of a condition to therapy. Overall postoperative satisfaction was assessed by the following question: "What is your overall postoperative satisfaction, on a scale from 0 to 10?". Relapse-free survival was analyzed using Kaplan-Meier curves. Results In total, 134 patients were included. With a median 12-year (range 10-15) follow-up, 52 patients (38.8%) underwent TVM surgery with Prolift, and Gynemesh was used 82 (61.2%). 91% patients felt that POP symptom improved based on the PGI-I scores, and most satisfied after operation. The recurrence rates of anterior, apical and posterior compartment prolapse were 5.2%, 5.2%, and 2.2%, respectively. No significant differences in POP recurrence, mesh-associated complications and urinary incontinence were noted between TVM surgery with Prolift versus Gynemesh. Conclusions Treatment of POP by TVM surgery exhibited long-term effectiveness with acceptable morbidity. The outcomes of the mesh kit were the same as those for self-cutmesh.